820 MCLA-145 is a bispecific IgG1 antibody that inhibits PD-1/PD-L1 signaling while simultaneously activating CD137 signaling on T cells. (9th November 2020) - Tacken, Paul; Wang, Liang-chuan; Klooster, Rinse; Loo, Pieter Fokko Van; Zhou, Jing; Mondal, Arpita; Liu, Yao-Bin; Kramer, Arjen; Condamine, Thomas; Volgina, Alla; Hendriks, Linda; Maaden, Hans van der; et al.
Abstract : Background: MCLA-145 is a CD137 x PD-L1 bispecific antibody that releases PD-L1 mediated T-cell inhibition and activates and expands T cells through agonism of CD137. Immune checkpoint inhibitors (ICI) against PD-(L)1 have demonstrated anti-tumor efficacy in a fraction of patients across a broad range of cancers. CD137 (4-1BB, tumor necrosis factor receptor superfamily 9) is an inducible costimulatory receptor transiently expressed on T cells after TCR engagement. CD137 signaling is triggered by receptor clustering and leads to enhanced cytokine production; T cell proliferation, survival, and effector function; and immunological memory formation. Targeting of PD-L1 and CD137 with MCLA-145 may achieve synergistic activity by simultaneously blocking the inhibitory checkpoint PD-L1 and activating tumor specific T cells through co-stimulation. Methods: We performed combinatorial functional screening of bispecific antibodies generated from high affinity inhibitory Fabs binding PD-L1 combined with a large and diverse panel of agonistic CD137 Fabs. Results: MCLA-145 was selected based on its in vitro potency in multiple primary human immune cell assays. Further, it displays an ability to reverse T cell suppression mediated by M2 macrophages or Tregs. MCLA-145 binds to a unique epitope in the cysteine rich domain 2 of CD137 that overlaps with the CD137L binding region, and all potent bAbs in the screen were able to bind to this region. MCLA-145 drives activation of CD137 and the degree of CD137 agonistic activity in T cells correlated with the expression level of PD-L1 on neighboring cells. Using proximity ligation assays and confocal microscopy we demonstrated that MCLA-145 clusters CD137 on the surface of T cells resulting in internalization. The binding location of MCLA-145 on CD137 may be optimal for the formation of 'immunological synapses' with PD-L1 expressing antigen presenting cells or tumors resulting in the potent activation of tumor specific cytotoxic T cells. Conclusions: These experiments demonstrate the dual anti-cancer activity of MCLA-145 in preclinical models: release of T-cell checkpoint inhibition through PD-L1; and activation and expansion of T cells through CD137, therefore overcoming T-cell exhaustion and increasing T-cell presence/activity (infiltration) in tumors. MCLA-145 is currently undergoing clinical development in an ongoing trial (NCT03922204 ). Ethics Approval: Animal experiments were performed according to guidelines for animal care of the local Animal Experiments Committee; Use of human blood cells from healthy volunteers was approved by the blood bank's Ethical Advisory Council.